Acute rheumatic fever and rheumatic heart disease in resource-limited settings. Issue 4 (17th March 2015) - Watson, Gabriella; Jallow, Bintou; Le Doare, Kirsty; Pushparajah, Kuberan; Anderson, Suzanne T
Abstract : Poststreptococcal complications, such as acute rheumatic fever (ARF) and rheumatic heart disease (RHD), are common in resource-limited settings, with RHD recognised as the most common cause of paediatric heart disease worldwide. Managing these conditions in resource-limited settings can be challenging. We review the investigation and treatment options for ARF and RHD and, most importantly, prevention methods in an African setting.